Windfall gains and labour supply: Evidence from the European household panel - Urban Sila; Ricardo M. Sousa (IZA Journal of Labor Economics, 2014)
We investigate whether workers adjust hours worked in response to windfall gains using data from the European Household Panel. The results suggest that a rise in unearned income has a negative (although small) effect on working hours. In particular, after receiving a windfall gain, individuals are more likely to drop out of the labour force and the effects become larger as the size of windfall increases. Furthermore, the empirical findings show that the impact of windfall gains on labour supply: (i) is more important for young and old individuals, (ii) is most negative for married individuals with young children, (iii) but can be positive for single individuals without children at the age of around 40 years. The latter effect can be explained by individuals using the windfall gain to set up their own business and become self-employed.
Keywords: D12; J22; 330; Windfall gains; Working hours